Transforming Higher Education in India: A Review of the National Education Policy 2020’s Impact - Shende, Ashay Devidas; Arpan A. Deshmukh, (AG Volumes, 2025)
Higher education is being approached from a different perspective thanks to "the National Education Policy (NEP) 2020", a historic overhaul in India's educational system. This study explores the many ways that NEP 2020 will affect students, higher education institutions, and the educational environment overall. According to the examination of several studies, cooperation between governmental organisations, academic institutions, students, industry partners, and the general public will be necessary for the NEP 2020 influence on higher education to be successful. NEP 2020 also brings about a significant change with the creation of Multidisciplinary Education and Research Universities (MERUs), which are based on U.S. and U.K. institutions and provide high-quality education in many fields. Furthermore, since the pandemic-driven digital revolution, "Open Distance Learning (ODL)", which presently serves 11% of students in higher education, is anticipated to grow rapidly.